1996
DOI: 10.1111/j.1365-2842.1996.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

A computerized method for evaluating balance of occlusal load

Abstract: In order to undertake a quantitative evaluation of balance occlusal load, the use of the Dental Prescale System was investigated. The method uses a test sheet that undergoes a colour-developing chemical reaction, for detecting contact area, and a computerized analysis system, for evaluating the balance of occlusal load. Twenty natural dentate subjects and 10 hemimaxillectomy patients participated in the study. Each subject bit a test sheet as hard as possible for 3 s. The balance of occlusal load was expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 3 publications
0
56
0
1
Order By: Relevance
“…[15][16][17][18][19] Dental Prescale is a 98-m thick horseshoe-shaped sheet wrapped with poly(ethylene terephthalate) film. The microcapsules in the sheet break and release a colorforming material at various occlusal pressures, 16 thus detecting OCs. An image scanner (FPD-703, Fuji Film Co, Tokyo, Japan) was used to determine OCA and estimate occlusal loads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] Dental Prescale is a 98-m thick horseshoe-shaped sheet wrapped with poly(ethylene terephthalate) film. The microcapsules in the sheet break and release a colorforming material at various occlusal pressures, 16 thus detecting OCs. An image scanner (FPD-703, Fuji Film Co, Tokyo, Japan) was used to determine OCA and estimate occlusal loads.…”
Section: Methodsmentioning
confidence: 99%
“…Dental Prescale (Fuji Film Co, Tokyo, Japan) can measure OCA quantitatively (in mm 2 ) by computer analysis of information obtained from a pressure-sensitive sheet (PSS). [15][16][17][18][19] The aim of this study was to test the hypothesis that long-term use of OAs causes significant changes in OCA by measuring and comparing OCA after longterm OA usage on dental study models with a PSS under constant load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This system is now being used in various fields of dental research, particularly by Japanese researchers [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][22][23][24][25][26][27][28][29][30][31][32][33] . These studies have suggested that this system might help evaluating masticatory function and could be applicable to general dental clinical work.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure sensitive sheets (Dental Prescale) are available for evaluating occlusal force, occlusal-contact area, and occlusal pressure [17][18][19][20] . The use of these sheets has developed as a method for the measurement of occlusal balance or dental implants.…”
Section: Introductionmentioning
confidence: 99%